The Future of Education: Trends in E-Learning and Digital Classrooms (Le Futur de l’Education : Tendances de l’apprentissage en ligne et celle des classes digitalisées) - KOTTIN, Assogba Evariste (My University, 2024)
This study explores the evolving landscape of education through the lens of e-learning and digital classrooms. By examining key trends such as artificial intelligence, gamification, wearable technology, and micro-learning, this research aims to provide a comprehensive overview of how these trends are reshaping educational experiences. Through questionnaires administered to 20 students and interviews conducted with 5 teachers, the study analyzes the impact and effectiveness of digital classrooms, highlighting both the benefits and challenges. The findings underscore the importance of embracing technological advancements suggesting to enhance learning accessibility, personalization, and engagement.
Keywords: Education; Digital; Artificial Intelligence; Gamification; Technology; E-learning.